PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERKARAKTER REALISTIC MATHEMATIC EDUCATION PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL KELAS VIII DI SMP NEGERI 3 SUWAWA - Nurma, Nurhayati Hasim; Usman, Kartin; Isa, Dewi Rahmawaty (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
The purpose of this study was to produce valid and practical student worksheets. This research was developed through the 4-D development model updated to 3-D define, design, and development.The results of the development obtained a student worksheet with realistic mathematic education characters on the material of a system of linear equations of two variables declared valid and feasible field trials based on the assessment of material experts and design experts. In expert validation, the product received a score of 85.18% from material experts and a score of 88.86% from media experts. In the assessment test to the teacher and 98.21% of the trial to students 96.47%. The students' worksheet through this trial received a very good response with very practical criteria and showed the interest of students in using LKPD during learning.